2018
DOI: 10.1176/appi.ajp.2018.17080913
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Randomized Clinical Trial of Prazosin for Alcohol Use Disorder

Abstract: Prazosin holds promise as a harm-reduction pharmacologic treatment for alcohol use disorder and deserves further evaluation by independent research groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 39 publications
2
35
0
3
Order By: Relevance
“…stress reactivity, measured via startle response and self-reported anxiety. These findings join with recent failures to replicate the treatment effects of prazosin for PTSD and AUD, suggesting the possibility that prazosin is a far less promising intervention for stress-related psychiatric disorders than originally believed (Petrakis et al 2016;Raskind et al 2018;Simpson et al 2018;Kleinman and Ostacher 2019). determination, and shock sensitivity assessment.…”
Section: Future Directions and Conclusionsupporting
confidence: 56%
“…stress reactivity, measured via startle response and self-reported anxiety. These findings join with recent failures to replicate the treatment effects of prazosin for PTSD and AUD, suggesting the possibility that prazosin is a far less promising intervention for stress-related psychiatric disorders than originally believed (Petrakis et al 2016;Raskind et al 2018;Simpson et al 2018;Kleinman and Ostacher 2019). determination, and shock sensitivity assessment.…”
Section: Future Directions and Conclusionsupporting
confidence: 56%
“…For example, Simpson et al . investigated the effect of prazosin, an α‐1 adrenergic receptor antagonist, on alcohol consumption in patients with alcohol use disorder by randomizing 92 study participants to receive either prazosin or placebo over a 12‐week period. Results from such RCTs are used to establish the standard of care for patients with substance use disorders and are cited as high‐quality supporting evidence for clinical practice guideline recommendations .…”
Section: Introductionmentioning
confidence: 99%
“…However, a fourth small trial (N = 41) observed no effect of doxazosin on its primary clinical outcomes in patients with AUD (Kenna et al 2016). More importantly, two more recent studies of prazosin that used somewhat larger sample sizes (N = 92-96) observed no effects on similar primary clinical outcomes in patients with AUD (Petrakis et al 2016, Simpson et al 2018). These latter null findings somewhat temper optimism for this class of medications to treat stress-induced relapse in humans (Kaye et al 2019).…”
Section: Stress-relevant Pharmacologic Treatmentsmentioning
confidence: 97%
“…Research from animal models suggested that the NE system was another natural pharmacologic target to reduce stress-induced relapse in humans (Kaye et al 2017, Verplaetse et al 2015. However, the null findings from two recent clinical trials of prazosin (Petrakis et al 2016, Simpson et al 2018 have somewhat tempered optimism for this class of medications to treat stress-induced relapse in humans. Prazosin also may not reduce CNS allostasis in response to either unpredictable or predictable shock as might have been expected from animal models (Kaye et al 2019).…”
Section: State Of the Evidencementioning
confidence: 99%